Integrating Rural Economic Development into the Adult Basic Education and Training (ABET) Curriculum as a Practice to Ensure Sustainable Livelihoods - Mafuwane , Barber Mbangwa (Journal of Education and Practice, 2024)
Purpose: The purpose of this study is to explore the integration of rural economic development initiatives and practices into the Adult Basic Education and Training curriculum with a view to leverage the people in rural communities to boost their productivity towards sustainable livelihoods. Methodology: This study adopted a qualitative approach in which the data was collected through focus group interviews. The participants were sampled from former and current ABET learners and their principal. The interviews were intended to solicit information about their farming project; how they started the farming and whether they were able to feed their families from the sale of their produce. Findings: The findings from the focus group interviews are that though they had support from the Kruger National Park, they still felt that the Department of Higher Education and Training (DHET) needed to intervene and make ABET a means for sustainable livelihoods for the beneficiaries. Unique contribution to public, policy and practice: This study contributed uniquely in the area of policy. The students proposed that the ABET curriculum needed to be restructured to include skills training to enable them to make a living after the ABET encounter.